Study of Fuel Oil Supply and Consumption in Indonesia - Akhmad, Akhmad; Amir, Amir (International Journal of Energy Economics and Policy, 2018)
The consumption of fuel oil (BBM) in Indonesia for the last ten years is increasing along with the increase in economic growth and the number of population. The increase in fuel oil consumption is not accompanied with the increase in domestic oil production. The research aimed to find out factors influencing fuel oil supply and consumption and forecasting the supply and consumption in Indonesia in the future. The research used time series data for 1997-2016. The research used econometrics model with simultaneous equation system. The model of simultaneous equation system built was consisted of 11 structural equations and 2 identic equations. The result of analysis indicated that factors influencing the supply of fuel oil were world oil price and the supply of oil in the previous year. In addition, factors influencing the consumption of fuel oil were fuel oil price and fuel oil consumption in the previous year. The result of forecasting indicates that fuel oil consumption in Indonesia up to 2025 is increasing in average of 4.07 percent for gasoline, 2.99 percent for kerosene, and 3.19 percent for diesel per year. In addition, the price of fuel oil in Indonesia was estimated to increase in average of 3.76 percent for gasoline, 3.87 percent for kerosene, and 3.19 percent for diesel, whereas, import of fuel oil increased in average of 4.83 percent per year. Keywords: Time Series, Simultaneous equations, Supply and Consumption of Fuel Oil, JEL Classifications: C32, Q4, Q47